1959
DOI: 10.1002/1529-0131(195904)2:2<114::aid-art1780020204>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Studies on adrenal cortical activity in patients with rheumatoid arthritis: The diurnal pattern and twenty-four hour levels of urinary total 17-hydroxycorticosteroids and 17-ketosteroids

Abstract: A h . These studies were supported by funds from the National I d t u t e of Arthritis and Metabolic Diseases, National Institutes of Health, U.S.P.H.S., and the A. H . Robins Company, Inc. Three of the authors (A. V., L. L. H. and J. H . McN.) are Trainees of the X&nal Institute of Arthritis and Metabolic Diseases, National Institutes of Health, U.S.P.H.S. 114ADRENAL CORTICAL ACXIVITY M RHEUMATOID ARTHRITIS 115 els have been found by several investigators,l2*21-23 while another reported low pIasma corticoid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1962
1962
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Subsequent attempts during the 1950s and early 1960s to critically analyze adrenal cortical relationships to the etiology of RA were inconclusive (5,6). In that era, time-and laborintensive methods were needed to assay the various urinary steroid metabolites and serum levels of the relevant hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent attempts during the 1950s and early 1960s to critically analyze adrenal cortical relationships to the etiology of RA were inconclusive (5,6). In that era, time-and laborintensive methods were needed to assay the various urinary steroid metabolites and serum levels of the relevant hormones.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 RA patients tend to be exposed to long-term physical and psychological stress during the course of their disease, and their neuroendocrine-immune system will become dysregulated, as has been reported elsewhere. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The stress-response system consists of neural (psychological), endocrine, and immune components which interact with each other. Thus, humoral and cellular factors related to these components will be changed by psychological or physical stress.…”
Section: Introductionmentioning
confidence: 46%
“…Previous studies 1 have shown that while the daily urinary excretion of 17-ketosteroids in patients with rheumatoid arthritis did not differ from that seen in normal subjects, the excretion of urinary 17-hydroxycorticosteroids was slightly diminished from the mean level observed in normal subjects, due to a lower output during the early morning hours. Although these mean urinary steroid values in patients with rheumatoid arthritis differed slightly from those found in normal subjects, they were not significantly different from those seen in patients with nonrheumatic chronic illnesses.…”
mentioning
confidence: 73%